Perancangan Analisis Risiko Pada Departemen Strategic Procurement di PT. X - Gabrielle Njoradi; I Nyoman Sutapa (Jurnal Titra, 2023)
Company X is a company engaged in the field of logistics and providing warehouse rents. Every necessity for internal and external (customer related) use is done and provided by the Strategic Procurement Department. In the process, there’s always a possibility for failure to happen such as potential risks that can obstruct procurement continuity. This suggests that riskmanagement planning is needed. This includes risk identification, risk assessment, and what risk treatment is suggested. From this research, four potential risks are identified that can obstruct the work process entirety at this company. Those risks are requests for non-existent goods, delay in responding to E-Procurement with the average of 31% for items and 32% for service, invoice forgery, and false procurement. To understand the root causes of these risks, a thorough analysis using the Five Whys Analysis method. To summarize this research, there are few suggested risk treatmentssuch as go live information dissemination, changing payment methods, and adding columns in E-Procurement. It is expected that the implementation of these recommended risk treatments will effectively mitigate the identified risks and contribute to a lower risk profile for the company.